A Possible Relationship Between Polymorphisms of Glutathione S-Transferase M1, P1 and T1 Genes and Rheumatoid Arthritis in Zahedan, Southeast Iran - Mohammad HASHEMI,; Ebrahim ESKANDARI-NASAB,; Zahra ZAKERI,; Mahdi ATABAKI,; Hamzeh REZAEI,; Gholamreza BAHARI,; Mohsen TAHERI4, (Archives of Rheumatology, 2012)
Objectives: This study aims to investigate the possible relationship between glutathione S-transferase (GST) gene (GSTM1, GSTT1, and GSTP1) polymorphisms and susceptibility to rheumatoid arthritis (RA). Patients and methods: This case-control study was conducted on 100 Iranian patients with RA (88 females, 12 males; mean age 44.1±13.2 years; range 17 to 75 years) and 100 healthy subjects (68 females and 32 males; mean age 45.7±9.6 years; range 23 to 70 years). The GSTP1 polymorphism was determined using a tetra amplification refractory mutation system-polymerase chain reaction (Tetra-ARMS-PCR) assay, whereas the GSTM1 and GSTT1 polymorphisms were analyzed by multiplex PCR. Results: The null genotype of GSTM1 was significantly higher in the patients with RA (78.0%) than in the control group (59.0%), and there was a risk factor for susceptibility to RA (OR=2.86, 95% CI=1.45-5.66, p=0.002). However, no significant difference was observed in the null genotype of GSTT1 among RA patients and healthy subjects (19% and 11%, respectively). There was no difference in the frequency distribution of the GSTP1 Ile105Val polymorphism between the groups (chi-square=1.69, p=0.429). Conclusion: Our findings showed that only the GSTM1 genetic polymorphism is associated with RA risk in a sample of the Iranian population.